Integrating nature-based solutions (NBS) into urban water management: a case study in tropical watershed - Oliveira, Ana Laura Pascucci de [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Rapid urbanization has significantly altered the natural hydrological cycle, exacerbating problems such as flooding, watercourse degradation, and reduced infiltration. This research examines the application of Nature-Based Solutions (NbS) - specifically rain gardens, constructed wetlands, and bioswales - as sustainable strategies for urban surface water management in the Água Comprida watershed, Bauru/SP, Brazil. The study employs an integrated approach combining geoenvironmental analysis, automated spatial data processing, and hydrological modeling using the Storm Water Management Model (SWMM) engine. Due to the high volume of geospatial data, customized pre-processing routines were developed to automate data extraction and parameterization for 330 drainage units. The research also addressed significant spatial and constructive constraints inherent to consolidated urban environments, which limited the feasibility of certain NbS typologies in densely built-up sectors. Despite these restrictions, the hydrological performance analysis demonstrated that NbS effectiveness is highly scale-dependent; while centralized units like constructed wetlands ensure downstream volumetric stability, decentralized units such as rain gardens and bioswales are decisive for local hydrological recovery. An integrated scenario revealed a hydraulic synergy effect, where the serial arrangement of units optimized total runoff retention beyond the sum of individual contributions. These results highlight that NbS performance is highly dynamic and sensitive to local site-specific conditions and rainfall intensity, suggesting that effectiveness should be evaluated beyond average capacity. Sensitivity analysis identified imperviousness and rain gardens’ berm height as the primary governing parameters for the system's hydrological response. Although performance declines under extreme hydrological stress, the findings confirm the technical feasibility and systemic benefits of nature-based interventions. This study provides important contributions for formulating public policies, offering both technical parameters and more robust guidelines to support the planning and prioritization of areas for NbS implementation in consolidated urban contexts.

A rápida urbanização alterou significativamente o ciclo hidrológico natural, exacerbando problemas como inundações, degradação de cursos d'água e redução da infiltração. Esta pesquisa examina a aplicação de Soluções baseadas na Natureza (SbN) — especificamente jardins de chuva, wetlands construídas e bioswales — como estratégias sustentáveis para o manejo de águas superficiais urbanas na bacia do Córrego Água Comprida, Bauru/SP, Brasil. O estudo utiliza uma abordagem integrada que combina análise geoambiental, processamento automatizado de dados espaciais e modelagem hidrológica através do software Storm Water Management Model (SWMM). Devido ao elevado volume de dados geoespaciais, foram desenvolvidas rotinas customizadas de pré-processamento para automatizar a extração de dados e a parametrização de 330 unidades de drenagem. A pesquisa também abordou restrições espaciais e construtivas significativas inerentes a ambientes urbanos consolidados, as quais limitaram a viabilidade de certas tipologias de SbN em setores densamente edificados. Apesar dessas restrições, a análise de desempenho hidrológico demonstrou que a eficácia das SbN é altamente dependente da escala; enquanto unidades centralizadas, como as wetlands construídas, garantem a estabilidade volumétrica a jusante, unidades descentralizadas, como jardins de chuva e bioswales, são decisivas para a recuperação hidrológica local. Um cenário integrado revelou um efeito de sinergia hidráulica, onde a disposição das unidades em série otimizou a retenção total do escoamento além da soma das contribuições individuais. Estes resultados destacam que o desempenho das SbN é altamente dinâmico e sensível às condições locais específicas e à intensidade da precipitação, sugerindo que a eficácia deve ser avaliada além da capacidade média. A análise de sensibilidade identificou a impermeabilidade e a altura da berma dos jardins de chuva como os principais parâmetros governantes para a resposta hidrológica do sistema. Embora o desempenho decline sob estresse hidrológico extremo, os achados confirmam a viabilidade técnica e os benefícios sistêmicos das intervenções baseadas na natureza. Este estudo fornece contribuições importantes para a formulação de políticas públicas, oferecendo parâmetros técnicos e diretrizes mais robustas para apoiar o planejamento e a priorização de áreas para a implementação de SbN em contextos urbanos consolidados.
Integração de soluções baseadas na natureza (SBN) na gestão hídrica urbana: um estudo de caso em uma bacia hidrográfica tropical
Keywords: Sustainable Development; Urban Hidrology; Environmental management; Hydrologic Models